Variation in occurrence and severity of major sorghum grain mold pathogens in India - BHARATI BHAT and S.S. NAVI, R.P. THAKUR*, V.P. RAO, G.D. AGARKAR, R.B. SOLUNKE (Indian Phytopathology, 2006)
Variation in occurrence and severity of pathogenic grain mold fungi were studied through a collaborative Sorghum Grain Mold Variability Nursery (SGMVN), consisting of 12 sorghum genotypes, that was established at five locations (Akola, Parbhani, Palem, Patancheru and Surat) during the three rainy seasons 2002-2004. Grain mold infection severity by the major pathogens was recorded at physiological maturity and on threshed grain, and grain colonization was measured using the blotter method. Among the fungal species, Fusarium spp., Curvularia lunata, Alternaria alternata and Phoma sorghina, in receding order, were predominant across locations and genotypes. Analysis of variance indicated highly significant effects of location, year, genotype and their interactions on grain mold severity and grain colonization by the four fungi. Grain colonization was highest by Fusarium spp. at Parbhani (54%), by C. lunata at Surat (45%), by A. alternata both at Parbhani (25%) and Patancheru (23%), and by P. sorghina at Patancheru (17%). Four of the sorghum genotypes (ICSV 96101, ICSV 95001, SPV 351/ICSV 1, and ICSV 91008) showed tolerance to mold infection (=3.0 severity) and these could serve as sources of grain mold resistance.